Bitcoin in Blockchain: A Survey - Zishan Ali, Syed; Sahu, Dolly; Sahu, Jatin (International Journal of Computer Sciences and Engineering, 2019)
The emerging technologies have highly incorporated with crypto-currencies and one of them is bitcoin which has a great effect on the digital marketing and day by day the amount of data associated with it is facing a steep growth and lots of security challenges are coming into play. In order to prevent the system from fraudulent transactions several methodologies have been used. In this study we have described how a digital currency can be maintained by the use of distributed decentralized ledger.